Prospects for the development of staff motivation using financial instruments (ESOP) - P. M. Abramyan (Путеводитель предпринимателя, 2021)
ESOP or employee participatory programs are designed to manage agency problems and motivate staff to increase productivity and, as a result, the financial results of the organization. Examples of such programs are considered in this work.